Perceived academic self-efficacy of adolescents and the relationship with physical activity - Neritzel Albisua; Gorka Martinez de Lahidalga Agirre; Malen Ruiz de Azua Larrinaga; Iker Etxeberria Atxa (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Given the challenges and levels of competitiveness that exist at the educational level, it is necessary to analyze the different factors that determine academic effectiveness, in consideration of sedentary tendencies and the need for physical activation in the school-age population, research to determine the relationships between academic self-efficacy with physical activity is carried out in this population. Methods: to carry out this project, a sample of 248 secondary and high school students was used, from whom characteristic information was collected on the perception of academic self-efficacy, on physical activity carried out using accelerometer over seven days, as well as the analysis of factors such as travel and sports practice. Results: it is shown that the variables surrounding rest show a negative correlation with academic efficiency, while the different levels of physical activity show a greater positive correlation with academic self-efficacy. Conclusions: moderate physical activity and MVPA show a greater benefit in perceived academic self-efficiency, while the rest variables show a negative relationship with academic efficiency.